The clinical impact of macrophage polarity after Kasai portoenterostomy in biliary atresia - Nagayabu, Kazuya; Fumino, Shigehisa; Shimamura, Ai; Sengoku, Yuki; Higashi, Mayumi; Iguchi, Masafumi; Aoi, Shigeyoshi; Saya, Shibata; Hirai, Maki; Ogi, Hiroshi; Miyagawa-Hayashino, Aya; Konishi, Eiichi; et al. (Frontiers in Pediatrics, 2024)
Introduction: Biliary atresia (BA) is a cholestatic hepatopathy caused by fibrosing destruction of intrahepatic and extrahepatic bile ducts, and its etiology has not been clearly revealed. In BA, liver fibrosis progression is often observed even after Kasai portoenterostomy (KPE), and more than half of cases require liver transplantation in their lifetime in Japan. Macrophages play an important role in liver fibrosis progression and are classically divided into proinflammatory (M1) and fibrotic macrophages (M2), whose phenotypic transformation is called "macrophage polarity." The polarity has been reported to reflect the tissue microenvironment. In this study, we examined the relationship between macrophage polarity and the post-KPE clinical course.Thirty BA patients who underwent KPE in our institution from 2000 to 2020 were recruited. Multiple immunostainings for CD68, CD163, CK19, and α-SMA were carried out on liver biopsy specimens obtained at KPE. ROC curves were calculated based on each clinical event, and the correlation with the clinical data was analyzed.The M2 ratio, defined as the proportion of M2 macrophages (CD163positive cells), was correlated inversely with the occurrence of postoperative cholangitis (AUC: 0.7602). The patients were classified into M2 high (n = 19) and non-high (n = 11) groups based on an M2 ratio value obtained from the Youden index (= 0.918). As a result, pathological evaluations (Metavir score, αSMA area fraction, and CK19 area fraction) were not significantly different between these groups. In mild liver fibrosis cases (Metavir score = 0-2), the M2 non-high group had a significantly lower native liver survival rate than the high group (p = 0.02). Moreover, 4 out of 8 cases in the M2 non-high group underwent early liver transplantation within 2 years after KPE.Conclusions: Non-M2 macrophages, including M1 macrophages, may be correlated with postoperative cholangitis, and the M2 non-high group in mild liver fibrosis cases had a significantly lower native liver survival rate than the high group, requiring early liver transplantation in this study. Preventing advanced liver fibrosis is a key factor in improving native liver survival for BA patients, and liver macrophages may play important roles in liver homeostasis and the promotion of inflammation and fibrosis.